Environmental Regulations and Industrial Enterprises Innovation Strategy: Evidence from China. Issue 4 (16th March 2022) - Li, Yuchen; Ma, Wenhao
ABSTRACT: This study examines whether environmental regulations affect innovation strategy of industrial enterprises. We show that strict environmental regulations negatively impact the innovation strategy of industrial enterprises, which leads the firms to be conservative, suggesting that the Porter hypothesis is not realized at this stage. We further demonstrate that environmental regulations have a long-term negative impact on company innovation strategy. Our findings are robust to when adjusting innovation strategy metrics and estimation method. In addition, strict environmental regulations have a more significant negative impact on heavy pollution enterprise. Overall, our results provide clear policy implications by revealing that achieving a win-win situation between environmental protection and enterprise innovation in emerging markets remains a challenge.